Towards Representing Load Dynamics on Primary Frequency Control-Constrained Unit Commitment - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2018)
The integration of non-dipatchable generation has increase the need for inertia and primary frequency response within power system operations. In such a scenario, load contribution to inertia and primary frequency response may play an important role in reducing both the estimated frequency control burden and the economic impact of increasing reserve capacity and ramping capability. Although some system operators have considered the contribution of load while estimating the reserve needs, the representation in the economic operation is very limited as dynamic aspects of inertia an ramping capability are not systematically represented. This work proposes a set of simplifying assumptions in order for a constraint to be included in the unit commitment formulation to account for load droop, ramping capability and inertia contribution. Numerical results on an illustrative example are provided. © 2018 IEEE.